Implementasi Kebijakan Anti-Dumping Oleh Uni Eropa Terhadap Impor Velg Mobil Asal Tiongkok - Kristianto, Alfons (Department of International Relations, Brawijaya University, 2022)
The steel industry plays an important role in the EU’s (European Union) economy. Its main product is car steel road wheels (velg), which are an important component for the automotive industry. Many imported Chinese car steel road wheels have harmed and disadvantaged domestic producers and manufacturers. This is caused by the dumping practice that China applies to its car and steel road wheel products. In fact, China's dumping practice has also been repeatedly implemented for a variety of products that are exported to the EU market. For that reason, the EU took firm action by implementing an anti-dumping policy on imports of Chinese car steel road wheels. This research aims to describe the anti-dumping policy, its implementation objectives, and its impacts. This research uses the pay-off structure theory of multilateral strategy to explore the idea of cooperation under anarchy, which is derived from the neoliberalism-institutionalism concept. This study also uses a qualitative narrative analysis method by including a research question, namely,